PENENTUAN WAKTU OPTIMUM PRODUKSI METABOLIT SEKUNDER ISOLAT BAKTERI ACTINOMYCETES DARI TANAH RHIZOSFER AKAR TANAMAN JARAK PAGAR (Jatropha curcas. L) TERHADAP BAKTERI PATOGEN - Fitriana Fitriana; Rusli Rusli (As-Syifaa Jurnal Farmasi, 2018)
The study of optimum time determination of secondary metabolite production of Actinomycetes bacteria isolate from Jatropha curcas L root of the soil (Jatropha curcas (L) of pathogenic bacteria has been done with the aim to determine pathogen bacteria that can be inhibited by Actinomycetes bacteria and determine the optimum time in producing secondary metabolite to pathogenic bacteria. The first phase of this study is to isolate Actinomycetes purification IBPT 01. Then performed a screening test of activity against pathogenic bacteria. Furthermore, the timing of production of antibiotics or secondary metabolites with bacterial fermentation Actinomycetes IBPT 01 begins on the 1st day until the 28th day and carried out the activity of antibiotics for 28 days. The results obtained in the screening test Actinomycetes bacteria activity IBPT code 01 provides antibacterial activity with category which has a diameter of 20 mm 11- barriers against 8 bacteria while one bacterium with diameter> 20 mm including strong category. Optimization results showed that the isolated bacteria Actinomycetes capable of producing secondary metabolites on 9 day, 8 day, 7 day, 4 day and 26 day. From this research can be concluded that the bacterial isolates of Actinomycetes IBPT 01 can provide the optimum time to produce different secondary metabolites.